Pengelolaan Alat-Alat dan Bahan Kimia Laboratorium IPA SMA di MGMP Kimia Kabupaten Donggala : Pengelolaan Alat-Alat dan Bahan Kimia Laboratorium IPA SMA di MGMP Kimia Kabupaten Donggala - Dwi Juli Puspitasari; husain Sosidi; prismawiryanti prismawiryanti (Universitas Serang Raya, 2023)
One of the problems that often arise in the world of education is the lack of learning resources, educational facilities and their use in assisting the learning process. The teacher's lack of knowledge in the use, maintenance and storage of equipment and chemicals makes the laboratory not utilized as a learning resource. The purpose of this service is to provide knowledge and skills to chemistry teachers regarding the management of chemical equipment and materials at the chemistry MGMP in Donggala district a. Community service activities were carried out at the MGMP Chemistry SMA Donggala Regency. Service activities are carried out by understanding of the provision of material regarding the management of equipment and chemicals, then followed by material on safety and work safety in the laboratory. Furthermore, carrying out field practice in the chemical laboratory in the form of guidance and assistance in the management of chemical equipment and materials. This activity is expected to increase understanding in chemistry learning as well as an increase in teacher quality which has a positive impact on improving student achievement.